Quantifying the spatiotemporal dynamics and multi-aspect performance of non-grain production during 2000–2015 at a fine scale. (June 2019) - Su, Yue; Li, Chenlu; Wang, Ke; Deng, Jinsong; Shahtahmassebi, Amir Reza; Zhang, Leping; Ao, Weijiu; Guan, Tao; Pan, Yi; Gan, Muye
Highlights: We explored the dynamics of NGPs from the perspective of time and space. We examined multi-aspect performance of different NGPs. Different NGPs showed distinct pattern of spatial clustering and regional disparity. NGPs could increase environmental pressure and the threat to grain security. The spatiotemporal dynamics of NGPs were linked to their multi-aspect performance. Abstract: In recent years, large quantities of cultivated land in China have been converted to non-grain production. There is a growing need to understand the spatiotemporal dynamics and multi-aspect performance of non-grain production to aid further agricultural development and ensure grain security. Multi-temporal high-resolution aerial photographs were used to investigate the trends of four categories of non-grain production (pond farming, duck rearing, nursery plantation and vegetable production) in the Tongxiang region of China from 2000 to 2015. Spatial analysis was then utilized to identify spatial autocorrelation and hotspots for different non-grain production categories. Finally, environmental and economic indicators were applied to assess the performance of different non-grain production categories from the perspective of environmental impact, economic benefits and grain security and to link the performance to the differences in dynamics. The results showed that the non-grain production in Tongxiang increased by 2460.68 ha from 2000 to 2015. The non-grain expansion in different periods was closely related to the central and local policy orientation. Environmental and economic analyses revealed that nursery plantation and pond farming consistently dominated in Tongxiang due to their low investment requirements, low environmental pressure and relatively high economic profit. All non-grain production categories exhibited strong spatial autocorrelation in 2000–2015, as evidenced by spatial analysis. Conspicuous regional disparities were also observed in the hotspots of different non-grain production categories, in part due to local traditions and the clustering effect. Non-grain production activities generated more pressure on the local environment than rice plantation despite high economic benefits. Furthermore, the expanding non-grain production in rural China will lead to an overestimation of grain outlook and jeopardize national grain security in the long run. Eco-agricultural systems, such as integrated rice-duck farming systems, could increase the likelihood of an economic and ecological win-win situation between non-grain production and grain cultivation.